The CORD (Couple Card) game in teaching the skill of oral reading ‏ ‏Seventh grade students of Government Secondary School 2 ‎Padang - Dianti Gustia ‎ Sari; Zainul Arifin (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
This dissertation was written with the subject of "CORD (Couple ‎Card) in learning loud reading skills in class VII students of Padang 2 ‎Public Middle School." This research is broadly and identified by ‎researchers, namely the ability to read a loud reading skills before ‎using the cord card game, and its use, and the effect of its use of the ‎ability to read loud reading skills. For grade VII students in Padang ‎‎2nd Middle School. The purpose of this study was to disclose the ‎ability to read loud reading skills before using the Cord Card (Couple ‎Card) game, and to reveal its usefulness, and to reveal the effect of its ‎use of loud reading skills of class VII students. Students at Padang ‎‎2nd Middle School. The research method used is an experimental ‎research method with a quantitative approach to field research. Data ‎collection tools used are interviews, tests and documentation. In ‎analyzing the data the researcher used the "T-Test" test using the ‎SPSS 21 program. However, before the "T" test was carried out the ‎researcher used the SPSS 21 program for the normal test and ‎homogeneity test, because the data must be normal and ‎homogeneous. The use of the CORD (Couple Card) game is effective ‎for the reading skills of class VII students of SMP Negeri 2 Padang. ‎This can be seen from the differences in learning outcomes before ‎using the CORD (Couple Card) game and after using it. Based on the ‎analysis of all control and experimental semester test results. The ‎‎"T" test (T test) shows that the result of the t test (-17.989) is greater ‎than the result of the t table (-23.298). The result of (Sig (2-tailed) is ‎‎0.00 and less than 0.05, the researcher concludes that the ‎morphological hypothesis (Ho) is rejected and the practical ‎hypothesis (Ha) is accepted‎